Template Synthesis, Structures and Spectral Behaviours of Binuclear Bimacrocyclic Pentaaza Complexes of Some Divalent Ions - Abdul-Ghani, Ahlam; Al-Najar, Nada (Iraqi Journal of Science, 2025)
Eight new binuclear metal complexes of pentaaza bimacrocyclic rings were prepared by condensation reactions of benzidine, formaldehyde, and o- phenylene diamine (o-p D) with one of the diketones: acetyl acetone (acac), dibenzoyl (DB), or dibenzoyl methane (DBM) in presence of Mn(II), Co(II), Cu(II), and Zn(II) chlorides, or with 1,2- dicyanobenzene (DCB) in presence of Zn(II) chloride in molar ratios of 1:4:4:2:2 respectively. Structures and bonding behaviour of complexes were characterized by elemental and thermal analyses, I.R and U.V-Visible spectra together with conductivity measurements and magnetic susceptibility. Octahedral geometries, were suggested for all prepared complexes. Five of the studied complexes exhibited fluorescence behaviour. Transitions and assignments were characterized from positions of excitation and emission bands in comparison with absorption spectra.